Global prevalence of urinary tract infection in pregnant mothers: a systematic review and meta-analysis - Salari, N.; Khoshbakht, Y.; Hemmati, M.; Khodayari, Y.; Khaleghi, A.a.; Jafari, F.; Shohaimi, S.; Mohammadi, M. (Elsevier, 2023)
Urinary tract infection (UTI) is a prevalent infection during pregnancy that can lead to complications for both the mother and the foetus. The objective of this systematic review and meta-analysis is to determine the global prevalence of UTIs (both symptomatic and asymptomatic) during pregnancy, based on previous studies in this area. Furthermore, this study aims to identify any factors that contribute to heterogeneity in the prevalence of UTIs during pregnancy.